Perceptions of Pay Satisfaction and Pay Justice: Two Sides of the Same Coin? - Peter Valet (Social Indicators Research, 2023)
Individual perceptions of pay satisfaction and pay justice are closely related social indicators. Notwithstanding their apparent resemblance, there are essential theoretical differences between those two concepts. Yet, we know little if people merely consider pay satisfaction and pay justice as two sides of the same coin. This paper theorizes two situations in which people's perceptions of pay satisfaction and pay justice should differ in meaningful ways. First, their pay level should affect people's self-interest and thus have a stronger effect on their pay satisfaction than on pay justice. Second, pay inequality in the workplace should affect people morally and thus should have a stronger effect on their pay justice perception than on pay satisfaction. These hypotheses were tested with linked employer-employee data collected in Germany (N0.167em=0.167em2.695). Results of regression analyses with multiple dependent variables show that people's pay satisfaction and pay justice perceptions increased with the level of their individual pay and decreased with the degree of workplace inequality. The pay effect was significantly stronger on pay satisfaction than on pay justice while the workplace inequality effects did not differ significantly. These results suggest that people under specific circumstances differentiate between pay satisfaction and pay justice. Consequently, researchers should consider that their results and conclusions might differ if they analyze pay satisfaction instead of pay justice and vice versa.
Keywords: 300; Pay level; Pay inequality; Pay satisfaction; Pay justice; Germany